Reimagining Solar Disinfection (SODIS) in a Microplastic Era: The Role of Pharmaceutical Packaging Waste in Biofilm Resilience and Resistance Gene Dynamics (International Journal of Scientific Research in Science and Technology, 2024)
The global escalation of antimicrobial resistance (AMR) and microplastic contamination presents a compounded threat to water safety, particularly in low-resource settings reliant on Solar Water Disinfection (SODIS) for microbiological purification. This conceptual paper reimagines the SODIS process in the context of increasing microplastic pollution derived from pharmaceutical packaging waste. It explores how microplastic particles, especially those leached from polyethylene and polypropylene-based blister packs and pill bottles, serve as abiotic substrates that facilitate persistent bacterial colonization and robust biofilm formation. These biofilms are not only more resistant to UV-A radiation—the primary inactivation mechanism in SODIS—but also act as hotspots for horizontal gene transfer (HGT), promoting the spread of antimicrobial resistance genes (ARGs) among microbial communities. This phenomenon undermines the fundamental premise of SODIS, which relies on solar-induced oxidative stress and DNA damage for bacterial inactivation. Furthermore, the presence of pharmaceutical residues adsorbed onto microplastics intensifies this risk by exerting selective pressure that favors resistant phenotypes. The paper proposes a systems-thinking framework that integrates pharmaceutical product design, waste stream management, and water treatment strategies to mitigate these compounding risks. It emphasizes the need for eco-design principles in pharmaceutical packaging, the incorporation of advanced materials with minimal leaching potential, and the promotion of decentralized plastic collection and recycling schemes. Additionally, it advocates for adaptive SODIS protocols that consider microplastic presence, possibly by integrating pre-filtration stages or synergistic photochemical enhancements. Policy implications are discussed, particularly the importance of regulating pharmaceutical plastic waste and embedding AMR surveillance within community-based water monitoring systems. Ultimately, this work underscores the interconnectedness of public health, material science, and environmental policy. Addressing AMR in a microplastic-contaminated world demands a multidisciplinary approach to ensure that water disinfection methods like SODIS remain effective, equitable, and resilient. The article provides a foundation for future empirical research, calling for experimental validation and real-world assessments of microplastic-induced SODIS failure pathways.